Alexithymia and risk preferences: Predicting risk behaviour across decision domains. (20th February 2018) - Panno, Angelo; Sarrionandia, Ainize; Lauriola, Marco; Giacomantonio, Mauro
Abstract : Risk‐taking is a critical health factor as it plays a key role in several diseases and is related to a number of health risk factors. The aim of the present study is to investigate the role of alexithymia in predicting risk preferences across decision domains. One hundred and thirteen participants filled out an alexithymia scale (Toronto Alexithymia Scale—TAS‐20), impulsivity and venturesomeness measures (I7 scale), and—1 month later—the Cognitive Appraisal of Risky Events (CARE questionnaire). The hierarchical regression analyses showed that alexithymia positively predicted risk preferences in two domains: aggressive/illegal behaviour and irresponsible academic/work behaviour. The results also highlighted a significant association of the alexithymia facet, externally oriented thinking (EOT), with risky sexual activities. EOT also significantly predicted aggressive/illegal behaviour and irresponsible academic/work behaviour. The alexithymia facet, Difficulty Identifying Feelings, significantly predicted irresponsible academic/work behaviour. The results of the present study provide interesting insights into the connection between alexithymia and risk preferences across different decision domains. Implications for future studies and applied interventions are discussed.